The Role of Parents in Improving Discipline among Table Tennis Extracurricular Students at SMPN 8 Cimahi - Yoesuff Palmy Rahman; Ricky Wirasasmita; Sony Hasmarita (STKIP Pasundan Press, 2025)
The writer's observation of the table tennis extracurricular activity at SMPN 8 Cimahi revealed issues related to parental involvement and student discipline, which have become obstacles for the school in achieving optimal coaching objectives. The research problem is formulated as follows: How does parental involvement contribute to improving the discipline of students participating in the table tennis extracurricular activity? This study employs a quantitative descriptive method with a survey approach. The population consists of 50 active students enrolled in the table tennis extracurricular activity at SMPN 8 Cimahi. Thesampling technique used is purposive sampling, resulting in a total of 25 respondents. The research instrument utilized in this study is a questionnaire, with data analyzed using frequency distribution techniques. The results indicate that 76% of parents’ roles are categorized as “good,” while 24% fall under the “fair” category. This reflects a generally positive level of parental involvement in supporting student discipline. These findings demonstrate that parentalinvolvement significantly influences the development of student discipline in extracurricular activities. Parents can reinforce students' character development, particularly discipline, through support provided both at home and within the school environment. In conclusion, in addition to teachers, parental involvement is also essential in improving student discipline. A persuasive approach should be applied to students categorized as having “fair” discipline, to help them build a stronger commitment toward positive behavioral changes in table tennis extracurricularactivities.